Pregnancy outcome following fetal reduction from dichorionic twins to singleton gestation - Greenberg, Gal; Bardin, Ron; Danieli-Gruber, Shir; Tenenbaum-Gavish, Kinneret; Shmueli, Anat; Krispin, Eyal; Oron, Galia; Wiznitzer, Arnon; Hadar, Eran (BMC pregnancy and childbirth, 2020)
There are still some controversies regarding the risks and benefits of fetal reduction from twins to singletons. We aimed to evaluate if fetal reduction from twins to singleton improves pregnancy outcome. Retrospective analysis of all dichorionic-diamniotic twin pregnancies, who underwent fetal reduction. Pregnancy outcome was compared to ongoing, non-reduced, dichorionic-diamniotic gestations. Primary outcome was preterm birth prior to 37 gestational weeks. Secondary outcomes included: preterm birth prior to 34 gestational weeks, gestational age at delivery, birthweight, small for gestational age, hypertensive disorders, gestational diabetes and stillbirth. Ninety-eight reduced pregnancies were compared with 222 ongoing twins. Preterm birth < 37 gestational weeks (39.6% vs. 57.6%, p < 0.001) was significantly lower in the reduced group compared to the ongoing twins' group. A multivariate analysis, controlling for parity and mode of conception, demonstrated that fetal reduction independently and significantly reduced the risk for prematurity (aOR 0.495, 95% CI -0.299-0.819). Subgroup analysis, similarly adjusted demonstrated lower rates of preterm delivery in those undergoing elective reduction (aOR = 0.206, 95% CI 0.065-0.651), reduction due to fetal anomalies (aOR = 0.522, 95% CI 0.295-0.926) and 1st trimester reduction (aOR = 0.297, 95% Cl 0.131-0.674) all compared to ongoing twins. A Kaplan-Meier survival curve showed a significant proportion of non-delivered women at each gestational week in the reduced group compared to non-reduced twins, after 29 gestational weeks. Fetal reduction from twins to singleton reduces the risk of preterm birth < 37 gestational weeks, but not for more severe maternal and perinatal complications.